Self-powered water meter for direct feedback - Tasic, Vojkan; Staake, Thorsten; Stiefmeier, Thomas; Tiefenbeck, Verena; Fleisch, Elgar; Tröster, Gerhard (IEEE 2012 - 3rd International Conference on the Internet of Things (IOT 2012), 2012)
Hot water usage accounts for 16% of household demand for energy, much more than lighting and cooking (5% each) and is comparable to electricity usage for appliances (21%). As a means of helping consumers to save hot water, we present a novel self-powered water consumption sensor that enables direct consumption feedback. We equipped 91 Swiss households with the sensors and recorded 3,164 individual showers during the period of three months. The presence of feedback during a shower resulted in the reduction of average shower water consumption from 79 l to 61 l (-22.2%) per day and household. In addition to savings attributable to already installed flow restrictors, an average household could conserve 6,400 l of drinking water and 210 kWh of heat energy (projected to one year). Furthermore, we show that the effects of direct feedback on water consumption did not decline over the course of the study.<br